Community Participation on the Kangpisman Program in Bandung City - Maulana, Dede Syaipul (Universitas Pendidikan Indonesia (UPI), 2021)
Abstract. The waste problem that is happening at this time must be the concern of all parties. The Bandung City Government has the Kangpisman program which is a collaborative movement between the government and the community in waste management. The programs set by the government must of course be supported by community participation. This study generally aims to determine community participation in the implementation of the Kangpisman program. The method used is a comparative study with descriptive analysis, namely comparing community participation in the implementation of the Kangpisman program in Kebon Pisang Village and Sukamiskin Village. The data analysis technique used is using percentage calculations. There are various factors that influence the community to participate in the Kangpisman program, the knowledge factor shows good results in both villages. Female gender shows a high percentage of participation. The work of housewives has a high level of participation. From the educational factor, the education level of Senior High School and Higher Education has a high percentage. The difference in the results of waste management in implementing the Kangpisman program in the two villages is due to differences in the level of community participation in implementing movements to reduce, separate and utilize waste.